Condom Access: Associations with Consistent Condom Use among Female Sex Workers in Two Northern Border Cities of Mexico - Muñoz, Fátima A. (2010)
To determine whether condom access is associated with consistent condom use among FSWs in Tijuana and Ciudad Juarez, between 2004 and 2006 we administered a questionnaire to 924 FSWs who reported unprotected sex with a client in the past two months. Of these women, 43% reported consistent (“often” or “always”) condom use; 74% said condoms were available; and 38% reported having access to free condoms. In a logistic regression, factors positively associated with consistent condom use were condom availability (AdjOR = 2.00; 95% CI: 1.32–3.03), condom affordability (AdjOR = 1.72; 95% CI: 1.25–2.38) and self–efficacy (AdjOR = 2.16; 95% CI: 1.54–3.04). Factors inversely associated with consistent condom use included poor financial status (AdjOR = 0.65; 95% CI: 0.47–0.90), methamphetamine use (AdjOR = 0.58; 95% CI: 0.40–0.83), alcohol use (AdjOR = 0.68; 95% CI: 0.49–0.96), and recent injection drug use (AdjOR = 0.62; 95% CI: 0.39–0.97). While increased condom availability may improve condom use among FSWs in general, interventions to broaden condom use among lower-income and drug-using FSWs are critically needed.